How Much Technological Progress is Needed to Make Solar Hydrogen Cost‐Competitive? - Schneidewind, Jacob (Advanced energy materials, 2022)
Cost‐effective production of green hydrogen is a major challenge for global adoption of a hydrogen economy. Technologies such as photoelectrochemical (PEC) or photocatalytic (PC) water splitting and photovoltaic + electrolysis (PV+E) allow for sustainable hydrogen production from sunlight and water, but are not yet competitive with fossil fuel‐derived hydrogen. Herein, open‐source software for techno‐economic analysis (pyH2A) along with a Monte Carlo‐based methodology for modelling of technological progress are developed. Together, these tools allow for the study of required technological improvement to reach a competitive target cost. They are applied to PEC, PC, and PV+E to identify required progress for each and derive actionable research targets. For PEC, it is found that cell lifetime improvements (>2 years) and operation under high solar concentration (>50‐fold) are crucial, necessitating systems with high space‐time yields. In the case of PC, solar‐to‐hydrogen efficiency has to reach at least 6%, and lowering catalyst concentration (<0.2 g L−1) by improving absorption properties is identified as a promising path to low‐cost hydrogen. PV+E requires ≈two or threefold capital cost reductions for photovoltaic and electrolyzer components. It is hoped that these insights can inform materials research efforts to improve these technologies in the most impactful ways. An open‐source software and Monte Carlo‐based methodology for the analysis of green hydrogen production are developed. These tools are used to analyze the required technological progress for cost‐competitive hydrogen production via photoelectrochemical and photocatalytic water splitting as well photovoltaic + electrolysis. Based on the results, actionable targets for materials research are derived.